A novel method of assessing balance and postural sway in patients with hypermobile Ehlers-Danlos syndrome - Whitmore, Miguel; Barker, Brittany; Chudej, Katie; Goines, Ciarra; Kester, Jenna; Campbell, Hannah; Jeffcoat, Anna; Castleberry, Brynn; Lowder, Thomas William (Frontiers in Medicine, 2023)
Patients with hypermobile Ehlers-Danlos syndrome (hEDS) frequently suffer from poor balance and proprioception and are at an increased risk for falls. Here we present a means of assessing a variety of balance and postural conditions in a fast and non-invasive manner. The equipment required is commercially available and requires limited personnel. Patients can be repeatedly tested to determine balance and postural differences as a result of disease progression and aging, or a reversal following balance/exercise interventions.